Factors contributing to the acceptance of Motor Takaful products amogst TM employees / Nurnadiah Mohd Dal - Mohd Dal, Nurnadiah (Faculty of Business and Management, 2010)
This research is a study of the factors contributing to the acceptance of motor Takaful products amongst TM employees. The objectives for this study are to identify the level of acceptance towards motor Takaful products, to determine the dominant factor that contributes to the acceptance of motor Takaful products amongst TM employees and to recommend on acceptance towards Motor Takaful products. In collecting the data, the researcher use method of primary and secondary data. For the primary data, researcher has distributed randomly, 100 questionnaires to TM employees. Secondary data came from the internet sources, books, journals and articles. The researcher used Statistical Package for Social Science (SPSS) Version 14.0 to analyze the data from the questionnaires to analyzing by used reliability analysis, correlation and regression linear. The findings from correlation and regression analysis indicate that all independent variable have strong significant relationship with acceptance of Motor Takaful product. Price has the greatest influence in quality acceptance of Motor Takaful product in TM.